Divergent trends in the burden of esophageal, gastric, and liver cancers in China - Yongjie Xu; Changfa Xia; Jiachen Wang; Yujie Wu; Wanqing Chen (Journal of the National Cancer Center)
Background: While China’s socioeconomic transformation has driven divergent trends in gastrointestinal cancers, comprehensive data on esophageal, gastric, and liver cancer burden remain limited. This study examines the global burden of esophageal, gastric, and liver cancers in 2022 and analyzes the trends of age-standardized incidence and mortality rate (ASRs) in China from 2000 to 2018, thereby providing evidence for the formulation of cancer control strategies. Methods: The global burden of esophageal, gastric and liver cancers including the estimated number of cases and deaths and the ASRs for incidence and mortality were from GLOBALCAN 2022 dataset. Data from 22 cancer registries in China were employed for the trend analysis of the ASRs for incidence and mortality of these three cancers. The Joinpoint model was used to compute the average annual percentage change (AAPC) of the incidence and mortality of the three cancers from 2000 to 2018. Results: Globally, esophageal, gastric and liver cancers accounted for 11.8 % of incident cancer cases and 19.1 % of cancer deaths. China bore a disproportionately high burden, representing 43.8 %, 37.0 %, and 42.4 % of global esophageal, gastric, and liver cancer cases respectively, and 42.1 %, 39.4 %, and 41.7 % of corresponding deaths. However, the ASRs for incidence and mortality for all three cancers declined significantly in China (2000–2018), with absolute case numbers decreasing for gastric and esophageal cancers during 2010–2022. Age-specific analysis revealed most pronounced declines in incidence and mortality in populations under 40 years old, with AAPCs of less than –6.0 % for esophageal cancer, around –4.0 % for gastric cancer, and approximately –2.0 % for liver cancer. Conclusions: China has achieved remarkable progress in controlling esophageal, gastric and liver cancers, yet these malignancies remain major public health challenges. Future efforts should intensify existing prevention measures while expanding screening programs, particularly for aging populations. These findings offer valuable insights for regions undergoing similar epidemiological transitions.